Antibiotic Resistance Pattern of Staphylococcus Aureus Isolated From Pediatrics With Ocular Infections: A 6-Year Hospital-Based Study in China - Zheng, Xiao-Yu; Choy, Bonnie Nga Kwan; Zhou, Ming-Ming; Zhao, Zheng-Yan (Frontiers in Pediatrics, 2021)
Staphylococcus aureus (S. aureus) is an important pathogen of ocular infections in pediatrics. The study aimed to identify the prevalence and resistance pattern of S. aureus, especially methicillin-resistant S. aureus (MRSA), in Chinese children with ocular infections. All patients with S. aureus infections were reviewed at a tertiary children’s hospital during 2015-2020, and those with ocular infections were investigated for susceptibility results. Of 1668 S. aureus strains, there were 177 unique isolates from ocular infection. Among them, 45 (25.4%) were MRSA and 132 (74.6%) were methicillin sensitive S. aureus (MSSA). The proportion of MRSA didn’t change over time. Most of the strains were obtained from Neonate ward and Ophthalmology department (n = 88, 49.7%, and n = 85, 48.0%, respectively), while eye secretion and pus were the main specimen types (n = 128, 72.3%, and n = 37, 20.9%, respectively). MRSA was significantly resistant against penicillins class (97.8%), erythromycin (71.1%), clindamycin (71.1%) and tetracycline (32.1%), with a high multidrug resistance (MDR) rate of 71.1%. However, MRSA was highly sensitive to levofloxacin. Resistance rates against erythromycin and ciprofloxacin as well as MDR percentage all increased among MSSA in children above 1 year of age, Ophthalmology department and outpatient population, and decreased in eye secretion specimen. The mean resistance percentage remained stable for MRSA and MSSA during the study period. The survey of ocular S. aureus pathogens in pediatrics and their antibiotic resistance patterns helps in clinical treatment. MRSA with many strains demonstrating MDR is highly prevalent in children with ocular infections in Southeast China. Levofloxacin is an effective topical antibiotic for ocular MRSA infection, while erythromycin has a high resistance rate. The antibiotic resistance patterns of MRSA and MSSA differs, and varies by different stratifications. A cautious use of antibiotics should be considered.